Molecular basis of cyclin-CDK-CKI regulation by reversible binding of an inositol pyrophosphate - Lee, Young-Sam (2007)
When Saccharomyces cerevisiae cells are starved of inorganic phosphate, the Pho80-Pho85 cyclin–cyclin-dependent kinase (CDK) is inactivated by the Pho81 CDK inhibitor (CKI). The regulation of Pho80-Pho85 is distinct from previously characterized mechanisms of CDK regulation: the Pho81 CKI is constitutively associated with Pho80-Pho85, and a small-molecule ligand, inositol heptakisphosphate (IP(7)), is required for kinase inactivation. We investigated the molecular basis of the IP(7)- and Pho81-dependent Pho80-Pho85 inactivation using electrophoretic mobility shift assays, enzyme kinetics and fluorescence spectroscopy. We found that IP(7) interacts noncovalently with Pho80-Pho85-Pho81 and induces additional interactions between Pho81 and Pho80-Pho85 that prevent substrates from accessing the kinase active site. Using synthetic peptides corresponding to Pho81, we define regions of Pho81 responsible for constitutive Pho80-Pho85 binding and IP(7)-regulated interaction and inhibition. These findings expand our understanding of the mechanisms of cyclin-CDK regulation and of the biochemical mechanisms of IP(7) action.